CHARACTERIZATION OF THE MUTATIONAL SPECTRUM AND ITS PROGNOSTIC SIGNIFICANCE IN PEDIATRIC ACUTE LEUKEMIA (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the frequency of gene mutations and their association with overall survival in pediatric acute leukemia (AL), including T-ALL, B-ALL, and AML.Materials and Methods: A retrospective secondary analysis of 763 pediatric patients with T-ALL (n=265), B-ALL (n=251), and AML (n=247) was performed using publicly available, de-identified data from St. Jude Cloud (GenomePaint/PeCan). Gene events (SNVs, indels, structural rearrangements, pathogenic fusions) were aggregated. Overall survival was analyzed using Kaplan–Meier and log-rank tests.Results: High-frequency mutations (>10%) included RUNX1 (46.4%), NRAS (45.9%), NOTCH1 (41.8%), ETV6 (37.9%), KRAS (30.9%), FLT3 (22.0%), MLLT3 (18.2%), WT1 (13.9%), KDM6A (13.0%), BCR (12.6%), TP53 (12.2%), and KIT (11.3%). RUNX1, NRAS, ETV6, and KRAS predominated in B-ALL and AML, whereas NOTCH1 was almost exclusive to T-ALL. Intermediate-frequency mutations (5–10%) included CD56, CBL, EZH2, FOXP1, TPK1, MSH2, MRD5, and KDM4C. NRAS mutation in B-ALL was significantly associated with poorer overall survival (p = 0.005); KRAS mutations showed no significant prognostic impact.Discussion and Conclusion: The mutational landscape varies markedly across AL subtypes and has potential clinical value for risk stratification and personalized treatment.
Keywords: Acute leukemia; gene mutation; prognosis; T-ALL; B-ALL; AML.